Teaching automotive suspension design to engineering students: Bridging the gap between CAD and CAE tools through an integrated approach. Issue 1 (January 2019) - Gadola, Marco; Chindamo, Daniel; Legnani, Giovanni; Comini, Marco
The paper presents an integrated approach to suspension design with educational purposes. A dedicated design tool was created to instruct automotive engineering students in the whole process of suspension design across the various CAE tools involved, from early kinematics studies to CAD, vehicle dynamics simulations and FEM modelling. The tool has given birth to a proven design procedure that the authors would like to share in this paper with focus on the educational side, although suspension kinematics design is not certainly a novel subject in itself. The tool includes geometries like the widely used McPherson strut, complex five-link schemes for high-end road cars, and typical racing car geometries like the so-called push/pull rod systems used on Formula 1 and Le Mans racecars. It has been applied successfully to various projects developed by professionals as well as by students, including the latest three Formula SAE (FSAE) single-seaters of the University of Brescia (Brescia, Italy) team. The paper is structured as follows. The introduction describes the role student design competitions play in higher engineering education, and within the frame of the Automotive Engineering course at UniBS in particular. A selection of relevant bibliography on the topic is listed. The Educational scenario section deals with the specific case of the Automotive Engineering course at UniBS and the requirements posed by student competitions, also in the frame of the Dublin Descriptors, and shows how suspension design can play a pivot role in a FSAE project. The A tool for suspension kinematics: requirements, description, solution section presents the software tool in itself. The math underlying the user interface is outlined. Finally, the integration features towards other CAE tools are presented with the related advantages.